Adaptive response of Bacillus subtilis to N-methyl-N'-nitro-N-nitrosoguanidine. - Hadden, C T (1983)
Cell extracts of Bacillus subtilis contain a methyltransferase that appears to remove the O6-methyl group from O6-methylguanine in DNA in situ. This reaction proceeds in a stoichiometric fashion, as in Escherichia coli. However, the basal level of the enzyme (approximately 240 molecules per cell) is significantly higher in B. subtilis than in E. coli. In addition, the methyltransferase level increases by an order of magnitude as a result of de novo protein synthesis after adaptive treatment with a low concentration of N-methyl-N'-nitro-N-nitrosoguanidine (MNNG), as in E. coli. Concomitant with adaptation, B. subtilis cells become more resistant to both killing and mutagenesis by a challenge dose of N-methyl-N'-nitro-N-nitrosoguanidine. We present evidence to support the hypothesis that the majority of N-methyl-N'-nitro-N-nitrosoguanidine-induced mutations in B. subtilis are of the guanine-to-adenine transition type.